Testing of the Ricardian Equivalence proposition: An Empirical Examination for Malaysia (1962-2006) - Ismail, Ismadi; Ismail, Abdul Ghafar; Amiruddin, Rosilawati (Gadjah Mada International Journal of Business, 2008)
This paper investigates the effects of debts and budgetary deficit on real variables using structural Vector Error Correction Model (VECM) method with long-run restrictions. We compare our estimates of the impulse responses with those based on levels Vector Auto-Regressive (VAR) with standard recursive order restrictions. The test is conducted on the Malaysian data covering the period of 1962-2006. The empirical results do not support the existence of âRicardian Equivalenceâ hypothesis. The effects of budgetary deficit and government spending have a significant influence on private consumption and private investment.